Immunological Consequences of Antihelminthic Treatment in Preschool Children Exposed to Urogenital Schistosome Infection. (5th June 2013) - Rujeni, Nadine; Nausch, Norman; Midzi, Nicholas; Cowan, Graeme J.; Burchmore, Richard; Cavanagh, David R.; Taylor, David W.; Mduluza, Takafira; Mutapi, Francisca
Abstract : Urogenital schistosomiasis, due to Schistosoma haematobium, is endemic in sub-Saharan Africa. Control is by targeted treatment with praziquantel but preschool age children are excluded from control programs. Immunological studies on the effect of treatment at this young age are scarce. In light of studies in older individuals showing that praziquantel alters antischistosome immune responses and responses to bystander antigens, this study aims to investigate how these responses would be affected by treatment at this young age. Antibody responses directed against schistosome antigens, Plasmodium falciparum crude and recombinant antigens, and the allergen house dust mite were measured in children aged 3 to 5 years before and 6 weeks after treatment. The change in serological recognition of schistosome proteins was also investigated. Treatment augmented antischistosome IgM and IgE responses. The increase in IgE responses directed against adult worm antigens was accompanied by enhanced antigen recognition by sera from the children. Antibody responses directed against Plasmodium antigens were not significantly affected by praziquantel treatment nor were levels of allergen specific responses. Overall, praziquantel treatment enhanced, quantitatively and qualitatively, the antiworm responses associated with protective immunity but did not alter Plasmodium -specific responses or allergen-specific responses which mediate pathology in allergic disease.